The Effect of Leadership Style on Employee Performance Mediated by Organizational Culture and Employee Motivation Bureau of Government and Regional Autonomy Regional Secretariat East Java Province - Ade Wimbo Brasrinanto; Susanto Sukiman (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2022)
Abstract. Employee performance is very large in determining organizational development so as to improve work performance and achieve organizational goals. Employee performance can be influenced by several factors. Leadership style, organizational culture and employee motivation are important in shaping employee performance. The purpose of this study was to analyze the effect of leadership style on employee performance mediated by organizational culture and employee motivation in the Bureau of Government and Regional Autonomy Regional Secretariat of East Java Province. This research is a causal research. The approach used is a quantitative method. The population in this study were all employees of the Bureau of Government and Regional Autonomy Regional Secretariat of East Java Province, totaling 75. The sampling technique used was saturated sampling technique, so the number of samples in this study were 75 respondents. Data collection techniques in this study were carried out by distributing questionnaires. The analysis technique in this study uses Partial Least Square(PLS).The results of this study indicate that: (1)Leadership style has a significant effect on organizational culture in the Bureau of Government and Regional Autonomy Regional Secretariat of East Java Province; (2) Leadership style has a significant effect on employee motivation at the Bureau of Government and Regional Autonomy Regional Secretariat of East Java Province; (3) Leadership style has a significant effect on employee performance at the Bureau of Government and Regional Autonomy of Regional Secretariat of East Java Province; (4) Organizational culture has a significant effect on employee performance at the Bureau of Government and Regional Autonomy of Regional Secretariat of East Java Province; (5) Employee motivation has a significant effect on employee performance at the Bureau of Government and Regional Autonomy Regional Secretariat of East Java Province Keywords: Leadership Style; Organizational Culture; Employee Motivation; Employee Performance